WOMEN'S EXPERIENCE OF CHILDBIRTH IN APPLYING HYPNOTHERAPY WITH MUSIC INTEGRATION - Eva Kartika Hasibuan; Yunida Turisna Octavia; Inggrit Puspita Sari; Sri Purwanti (Jurnal Ilmiah Keperawatan, 2026)
Background: The maternal mortality rate in North Sumatra in 2020 remained high at 187 per 100,000 live births. Anxiety during pregnancy, with a prevalence of 18.2–24.6%, can increase the risk of complications such as premature delivery, low birth weight, and postpartum depression. Non-pharmacological efforts such as music therapy and hypnotherapy have the potential to reduce anxiety in pregnant women. Objective: This study aimed to explore the experiences of women in labor who received music-integrated hypnotherapy to alleviate anxiety. Methods: This type of research is qualitative with a descriptive phenomenological approach. The population in this study is women in labor with a total of 10 participants and data saturation has been achieved, sampling techniques using purposive sampling, data collection tools namely interview guides, voice recorders and field notes. Data processing through the collaizi approach and NVivo version 14 (trial). Ethical approval was obtained from the Health Research Ethics Committee of Muhammadiyah North Sumatera University under approval number 1528/KEPK/FKUMSU/2025. Results: The results of the research obtained resulted in 4 (four) themes, namely experiencing anxiety before the implementation of Hypnotherapy; Implementation of Hypnotherapy; Getting support in the implementation of Hypnotherapy and Developing confidence and expextations for Continuity. Conclusion: The results of the study revealed that mothers interpreted the application of hypnotherapy integrated with music as an experience that had a positive impact during pregnancy to the delivery process.